Insular activation during reward anticipation reflects duration of illness in abstinent pathological gamblers - Tsurumi, Kosuke; Kawada, Ryosaku; Yokoyama, Naoto; Sugihara, Genichi; Sawamoto, Nobukatsu; Aso, Toshihiko; Fukuyama, Hidenao; Murai, Toshiya; Takahashi, Hidehiko (Frontiers in Psychology, 2014)
Pathological gambling (PG) is a chronic mental disorder characterized by a difficulty restraining gambling behavior despite negative consequences. Although brain abnormalities in patients with substance use disorders are caused by repetitive drug use and recover partly with drug abstinence, the relationship between brain activity and duration of illness or abstinence of gambling behavior in PG patients remains unclear. Here, using functional magnetic resonance imaging, we compared the brain activity of 23 PG patients recruited from a treatment facility with 27 demographically-matched healthy control subjects during reward anticipation, and examined the correlations between brain activity and duration of illness or abstinence in PG patients. During reward anticipation, PG patients showed decreased activity compared to healthy controls in a broad range of the reward system regions, including the insula cortex. In PG patients, activation in the left insula showed a significant negative correlation with illness duration. Our findings suggest that insular activation during reward anticipation may serve as a marker of progression of pathological gambling.